An ecophysiological model for interspecific competition, applied to the influence of chenopodium-album l on sugar-beet .2. Model evaluation - Kropff, M.J.; SPITTERS, C. J. T.; SCHNIEDERS, B.J.; JOENJE, W.; DE GROOT, W. (Wiley, 1992)
: Résumé: ZusammenfassungA simulation model for crop‐weed competition, parameterized for sugar beet and Chenopodium album L., was validated with experimental data from five field experiments. Between the experiments, 98% of the variation in yield loss, ranging from –6 to 96%, was explained by the simulation model. After validation, the model was used to analyse the backgrounds of the distinct differences in yield loss between the experiments. The contribution of differences in water shortage appeared to be negligible. The number of days between crop and weed emergence, which ranged from 0–31 days, appeared to be the main factor responsible for the differences in yield loss between the experiments (96%). Further analysis showed that water shortage only influences competitive strength of the weeds when overtopped by the crop. Temperature in the period between crop and weed emergence appeared to be an important factor determining the competitive relationships. It is concluded that the period between crop and weed emergence should be expressed as a developmental measure (i.e. degree days) instead of days. Morphological characteristics such as the relative growth rate of leaf area in early growth phases, specific leaf area and height increase largely determined the competitive strength of a species. The effect of physiological characteristics, such as maximum rate of leaf photosynthesis, was less significant. Un modèle écophysiologique pour la compétition interspécifique appliquéà l'influence de Chenopodium album L. sur la betterave sucrière II. Evaluation du modèleUn modèle de simulation de la compétition culture/adventice, paramétré pour la betterave et Chenopodium album L. a été validé avec des données expérimentales issues de 5 essais de plein champ. Entre les essais, 98% de la variation de perte de rendement, allant de – 6 à 96%étaient expliqués par le modèle de simulation. Après validation, le modèle a été utilisé pour analyser les courbes des différences de pertes de rendement entre les essais. Les différences liées au manque d'eau sont négligeables. Le nombre de jour entre la levée de la culture et de l'adventice qui a varié de 0 à 31 jours, est apparu être le principal facteur responsable des différences entre perte de rendement entre les essais (96%). D'autres analyses ont montré que le manque d'eau influence seulement la vigueur de compétition des adventices quand elles sont recouvertes par la culture. La température de la période entre la levée de la culture et de l'adventice apparaît être un important facteur déterminant les relations de compétition. II estconclu que la période entre la levée de la culture et de l'adventice devrait être exprimée en mesure de développement (par exemple en degrés/jour plutôt qu'en jour). Des caractéristiques morphologiques comme le taux de croissance relative de la surface foliaire dans les premiers stades, la surface spécifique foliaire et l'augmentation de hauteur, déterminent grandement la vigueur de compétition d'une espèce. Les effets des caractéristiques physiologiques comme le taux maximum de la photosynthèse foliaires sont moins significatifs. Ein ökophysiologisches Modell der interspezifischen Konkurrenz von Chenopodium album auf die Zuckerrübe. II. ValidierungEin Simulationsmodell zur Konkurrenz zwischen Kulturpflanze und Unkraut, hier Zuckerrübe (Beta vulgaris L.) und Weißer Gänsefuß (Chenopodium album L.), wurde anhand von Daten aus 5 Freilandversuchen validiert. 98% der Variation der Ertragsverluste, die zwischen –6 und 96% lagen, wurden anhand des Modells erklärt. Nach der Validierung wurden mit dem Modell die Bestimmungsgründe für die jeweiligen Unterschiede der Ertragsverluste analysiert. Der Beitrag von Unterschieden des Wassermangels erschien als vernachlässigbar. Die Konkurrenzkraft der Unkräuter wurde durch Wassermangel nur beeinflußt, wenn sie von der Kulturpflanze überwachsen wurden. Die Anzahl der Tage zwischen dem Auflaufen der Kulturpflanze und der Unkrautart, das 0 bis 31 Tage auseinander lag, erwies sich als größter Faktor für die Ertragsverlustunterschiede (96%). Die Temperatur während der Keimperiode war für die Bestimmung der Konkurrenzbeziehungen wichtig. Deshalb sollte die Keimperiode zwischen Kulturpflanze und Unkraut mit einem Entwicklungsmaß (d.h. Temperatursummen) anstatt in Tagen bemessen werden. Morphologische Kenndaten wie relative Wuchsrate der Blattfläche in frühen Entwicklungsstadien, spezifische Blattfläche und Wuchshöhe bestimmten die Konkurrenzkraft einer Art in hohem Maße. Physiologische Daten wie maximale Photosyntheserate waren weniger signifikant.